Analisis Kemiskinan dan Pertumbuhan Ekonomi di Bali: Model TSLS - Iswara, Putu Noppy; Meydianawathi, Luh Gede; Indrajaya, I Gusti Bagus; Adigorim, I Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 11, November 2016 (pp. 1168 - 1346), 2016)
This research aimed to analyze reciprocal effect between poverty and economic growth in the province of Bali during the period 2009-2014. The analysis technique used this research is Two-Stage Least Square (TSLS). This research examined the effect of 5 variables: economic growth, minimum wage, education, health, and unemployment to poverty, and the impact of 4 variables: poverty, labor, local revenue, and investment to economic growth. The analysis shows that there is noreciprocal effect between poverty and economic growth in Bali province during the period of the research. Meanwhile, variables minimum wage, education and health have a significant effect on poverty, on the other hand, labor force have a significant effect on economic growth. In order to reducing poverty through economic growth, the government is expected to focus on productive sectors in every region combined with labor and technology so that will improve the welfare of people in each area.
Keywords: poverty, economic growth, Two-Stage Least Square